Tow-tank testing of a 1/20th scale horizontal axis tidal turbine with uncertainty analysis. (September 2015) - Doman, Darrel A.; Murray, Robynne E.; Pegg, Michael J.; Gracie, Katie; Johnstone, Cameron M.; Nevalainen, Thomas
Highlights: Experimental performance data of a three-bladed 1/20th scale NREL S814 tidal turbine rotor. Description of theory behind calculated values, and overview of test setup and procedures. Complete uncertainty analysis showing high level of reliability of test results. Rotor stability and Reynolds number scaling effects discussed. Abstract: Tidal turbine developers and researchers use small scale testing (i.e. tow tank and flume testing) as a cost effective and low risk way to conduct proof-of-concept studies and evaluate early stage device performance. This paper presents experimental performance data for a three-bladed 1/20th scale NREL S814 tidal turbine rotor, produced at the 4.6 × 2.5 m and 76 m long Kelvin Hydrodynamics Laboratory tow tank at Strathclyde University. The rotor performance was characterised from very low tip speed ratios to runaway for four carriage speeds. A maximum C P of 0.285 and a maximum C T of 0.452 were recorded at tip speed ratios of 3.53 and 4.45 for a carriage speed of 1 m/s. The uncertainty in the instrument calibration and experimental measurements was quantified, allowing accurate representation of the experiments in numerical models. The methodology behind the uncertainty calculations is described in this paper. The uncertainty in the experimental measurements was found to be less than 5% for over 87% of the tests. Reynolds number scaling effects were found to be influential on the rotor performance in the range of velocities tested.